Quality nursery plant production in apple by altering shoot growth formation pattern - Kumawat, K L; Raja, W H; Sharma, O C; Singh, D B (Indian Horticulture, 2020)
With the rapid adoption of vertical planner orchard planting systems particularly Tall Spindle for apple high density planting plantation, apple growers need to utilize feathered nursery plants to ensure early production, which help to cover the substantial increased cost for establishment of high density orchard. However, mostly the planting material produced and sold, is un-branched, 60-90 cm, small caliper plant with one-year-old tops which do not suit to the demand of commercial apple orchardists utilizing high density planting system. The country is spending a lot of money for import of feathered nursery plants from other countries. Moreover, being a large canopy size, feathered nursery plants are difficult to carry/transport as they require specific care during packaging and transportation. Therefore, in present scenario, it has become necessary to develop a nursery management technique to stimulate development of feathers on one year old nursery plant so that apple nurseries can produce the high quality well-feathered plants suitable for advanced high density orchard planting system.